Bacterial Adhesion and Surface Roughness for Different Clinical Techniques for Acrylic Polymethyl Methacrylate - Lucas Costa de Medeiros Dantas; João Paulo da Silva-Neto; Talita Souza Dantas; Lucas Zago Naves; Flávio Domingues das Neves; Adérito Soares da Mota (International Journal of Dentistry)
This study sought to assess the effect of different surface finishing and polishing protocols on the surface roughness and bacterial adhesion (S. sanguinis) to polymethyl methacrylates (PMMA). Fifty specimens were divided into 5 groups (n=10) according to their fabrication method and surface finishing protocol: LP (3 : 1 ratio and laboratory polishing), NF (Nealon technique and finishing), NP (Nealon technique and manual polishing), MF (3 : 1 ratio and manual finishing), and MP (3 : 1 ratio and manual polishing). For each group, five specimens were submitted to bacterial adhesion tests and analyzed by scanning electron microscopy (SEM). Two additional specimens were subjected to surface topography analysis by SEM and the remaining three specimens were subjected to surface roughness measurements. Data were compared by one-way ANOVA. The mean bacterial counts were as follows: NF, 19.6±3.05; MP, 5.36±2.08; NP, 4.96±1.93; MF, 7.36±2.45; and LP, 1.56±0.62 (CFU). The mean surface roughness values were as follows: NF, 3.23±0.15; MP, 0.52±0.05; NP, 0.60±0.08; MF, 2.69±0.12; and LP, 0.07±0.02 (μm). A reduction in the surface roughness was observed to be directly related to a decrease in bacterial adhesion. It was verified that the laboratory processing of PMMA might decrease the surface roughness and consequently the adhesion of S. sanguinis to this material.